Survival in bladder and upper urinary tract cancers in Finland and Sweden through 50 years. - Kari Hemminki; Asta Försti; Akseli Hemminki; Börje Ljungberg; Otto Hemminki (PLoS ONE)
Survival has improved in bladder cancer but few studies have considered extended periods or covered populations for which medical care is essentially free of charge. We analyzed survival in urothelial cancer (UC, of which vast majority are bladder cancers) in Finland and Sweden over a 50-year period (1967-2016) using data from the NORDCAN database. Finland and Sweden are neighboring countries with largely similar health care systems but higher economic resources and health care expenditure in Sweden. We present results on 1- and 5-year relative survival rates, and additionally provide a novel measure, the difference between 1- and 5-year relative survival, indicating how well survival was maintained between these two periods. Over the 50-year period the median diagnostic age has increased by several years and the incidence in the very old patients has increased vastly. Relative 1- year survival rates increased until early 1990s in both countries, and with minor gains later reaching about 90% in men and 85% in women. Although 5-year survival also developed favorably until early 1990s, subsequent gains were small. Over time, age specific differences in male 1-year survival narrowed but remained wide in 5-year survival. For women, age differences were larger than for men. The limitations of the study were lack of information on treatment and stage. In conclusion, challenges are to improve 5-year survival, to reduce the gender gap and to target specific care to the most common patient group, those of 70 years at diagnosis. The most effective methods to achieve survival gains are to target control of tobacco use, emphasis on early diagnosis with prompt action at hematuria, upfront curative treatment and awareness of high relapse requiring regular cystoscopy follow up.